2021
DOI: 10.1186/s12864-020-07323-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathways involved in pony body size development

Abstract: Background The mechanism of body growth in mammals is poorly understood. Here, we investigated the regulatory networks involved in body growth through transcriptomic analysis of pituitary and epiphyseal tissues of smaller sized Debao ponies and Mongolian horses at the juvenile and adult stages. Results We found that growth hormone receptor (GHR) was expressed at low levels in long bones, although growth hormone (GH) was highly expressed in Debao po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…As an important breed in northern China, Mongolian horses have rich genomic diversity ( 21 ) and have a variety of excellent traits, such as adaptability, cold resistance, roughage resistance, disease resistance, and good stamina ( 22 , 23 ). Thoroughbred horses, a horse species bred in 17th-century Britain, were manually selected to meet the desired conditions of speed, temperament, and body size ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an important breed in northern China, Mongolian horses have rich genomic diversity ( 21 ) and have a variety of excellent traits, such as adaptability, cold resistance, roughage resistance, disease resistance, and good stamina ( 22 , 23 ). Thoroughbred horses, a horse species bred in 17th-century Britain, were manually selected to meet the desired conditions of speed, temperament, and body size ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…DLX5, DKK1 and WNT2 are mainly enriched in the WNT signaling pathway and are involved in bone production, renewal and healing by regulating the expression of osteogenic coregulators, which are capable of influencing body size and thoracic vertebrae number in pigs. [55][56][57][58][59]. BS pigs are classified as large, medium, or small, probably due to differences in the expression and regulatory effects of osteogenic genes that differentiate their body sizes.…”
Section: Discussionmentioning
confidence: 99%
“…By downregulating the MAPK signaling cascade, GHR may reduce Debao horse height. The candidate genes Sox9 and Sox11 were found to promote the early occurrence of bio mineralization and epiphyseal closure in Debao ponies [51]. The candidate gene ADAMTS15 is associated with muscle development, such as myoblast fusion in thoroughbred horses [69].…”
Section: Discussionmentioning
confidence: 99%
“…The genes MRas and ATF3 in the GHR shed light on the genetics of the Debao pony of small stature. To understand the genetic basis of short size, genes such as ECM, ALPL, IHH, MMP23, TIMP4, COL10A1, Sox9, Sox6, Sox8, Sox11, COL2A1, and COL9A1 have been identified in the juvenile stage of the Debao horse [51]. A recent study showed that the genes TBX3, TBX5, and HMGA2 play a role in the genetic underpinnings of Chinese pony dwarfism [52].…”
Section: Introductionmentioning
confidence: 99%